(untitled) (Third Sector Social Economic Review, 2017)
Organizing farmers effectively is one of very important tools to develop the agricultural sector. Although the farmers’ organizations in Turkey had shown significant improvement in quantity, they could not provide sufficient services to their members. This fact was partly related with the problems arising from the legislation inadequacy. The main aim of this research was to expose an assessment of the legislation on the farmer organizations in Turkey under recent developments and to recommend necessary changes in the legislations. The main material of this research was the legislation on the farmer organizations. The research results showed that there were many legislations on the farmer organizations in Turkey and these legislations established different kind farmer organizations. A civil and democratic approach was not taken as a basis on establishing them. The same aims were given to the different farmer organizations, different public institutions were authorized on auditing the farmer organizations. Their structure did not adequately reflect their member needs and current developments. The farmers had to be a member to the numerous farmer organizations to meet their different needs. In order to organize the farmers effectively, the current legislation on the farmer organizations should be simplified with a general framework. For this, it is necessary to discuss and create a single organizational structure which can meet all needs of the farmers. The government should also provide all public services to this farmer organization though only one public institution.